2014
DOI: 10.3389/fphys.2013.00415
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for pancreatic cancer: underlying mechanisms and potential targets

Abstract: Purpose of the review: Pancreatic cancer is extremely aggressive, forming highly chemo-resistant tumors, and has one of the worst prognoses. The evolution of this cancer is multi-factorial. Repeated acute pancreatic injury and inflammation are important contributing factors in the development of pancreatic cancer. This article attempts to understand the common pathways linking pancreatitis to pancreatic cancer.Recent findings: Intracellular activation of both pancreatic enzymes and the transcription factor NF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
80
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(82 citation statements)
references
References 194 publications
0
80
0
2
Order By: Relevance
“…Repeated insults such as smoking lead to the activation of nuclear transcription factor kB, which is involved in various inflammatory signaling pathways. It induces a number of cytokines within the pancreas, such as IL-1, IL-2, IL-6, IL-8, IL-12, and TNF-a (9,33). Indeed, a previous Italian cross-sectional study in 1123 participants showed that higher fasting plasma concentrations of EPA and DHA were inversely associated with plasma concentrations of IL-6 and TNF-a, independently of several confounding factors (35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Repeated insults such as smoking lead to the activation of nuclear transcription factor kB, which is involved in various inflammatory signaling pathways. It induces a number of cytokines within the pancreas, such as IL-1, IL-2, IL-6, IL-8, IL-12, and TNF-a (9,33). Indeed, a previous Italian cross-sectional study in 1123 participants showed that higher fasting plasma concentrations of EPA and DHA were inversely associated with plasma concentrations of IL-6 and TNF-a, independently of several confounding factors (35).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic inflammation is deeply involved in the development of pancreatic cancer (32,33). n-3 PUFAs have anti-inflammatory and immunoregulatory effects (9,34).…”
Section: Discussionmentioning
confidence: 99%
“…Of these, pancreatitis (including its acute and chronic forms) is one of the most frequently studied diseases. Although the pathogenesis mechanisms underlying the role of pancreatitis in PC etiology are still unclear, the molecular pathway for this association had been put forward by several hypotheses (Sakorafas et al, 2012;Gukovsky et al, 2013;Pinho et al, 2014;Kolodecik et al, 2014). Just like other benign diseases are associated with an increased cancer risk in the target organs (e.g., hepatitis and liver cancer, gastritis and gastric cancer), increased cell turnover and defective DNA repair in pancreatitis cases could lead to the occurrence of PC.…”
Section: Introductionmentioning
confidence: 99%
“…It contains adipocytes, connective tissue matrices, nerve tissue, stromovascular cells, and immune cells (11). Excess adiposity leads to chronic, low-grade inflammation, which, among other factors, has been implicated in cancer development (12)(13)(14)(15)(16)(17). Increasing adiposity may act via the dysregulated secretion of proinflammatory cytokines, chemokines, and adipokines to contribute to the development of cancer.…”
Section: Introductionmentioning
confidence: 99%